Angiotensinogen Exerts Effects Independent of Angiotensin II. Issue 2 (February 2016) - Lu, Hong; Wu, Congqing; Howatt, Deborah A.; Balakrishnan, Anju; Moorleghen, Jessica J.; Chen, Xiaofeng; Zhao, Mingming; Graham, Mark J.; Mullick, Adam E.; Crooke, Rosanne M.; Feldman, David L.; Cassis, Lisa A.; et al.
Abstract : Objective—: This study determined whether angiotensinogen (AGT) has angiotensin II–independent effects using multiple genetic and pharmacological manipulations. Approach and Results—: All study mice were in low-density lipoprotein receptor −/− background and fed a saturated fat–enriched diet. In mice with floxed alleles and a neomycin cassette in intron 2 of the AGT gene (hypoAGT mice), plasma AGT concentrations were >90% lower compared with their wild-type littermates. HypoAGT mice had lower systolic blood pressure, less atherosclerosis, and diminished body weight gain and liver steatosis. Low plasma AGT concentrations and all phenotypes were recapitulated in mice with hepatocyte-specific deficiency of AGT or pharmacological inhibition of AGT by antisense oligonucleotide administration. In contrast, inhibition of AGT cleavage by a renin inhibitor, aliskiren, failed to alter body weight gain and liver steatosis in low-density lipoprotein receptor −/− mice. In mice with established adiposity, administration of AGT antisense oligonucleotide versus aliskiren led to equivalent reductions of systolic blood pressure and atherosclerosis. AGT antisense oligonucleotide administration ceased body weight gain and further reduced body weight, whereas aliskiren did not affect body weight gain during continuous saturated fat–enriched diet feeding. Structural comparisons of AGT proteins in zebrafish, mouse, rat, and human revealed 4 highly conserved sequences within the des(angiotensin I)AGT domain. des(angiotensin I)AGT, through adeno-associated viral infection in hepatocyte-specific AGT-deficient mice, increased body weight gain and liver steatosis, but did not affect atherosclerosis. Conclusions—: AGT contributes to body weight gain and liver steatosis through functions of the des(angiotensin I)AGT domain, which are independent of angiotensin II production. Abstract : Supplemental Digital Content is available in the text.